2011
DOI: 10.1128/jcm.00625-11
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Intravascular-Catheter-Related Bacteremia Caused by Delftia acidovorans in a Hemodialysis Patient

Abstract: We report the first case of recurrent intravascular-catheter-related bacteremia in a pediatric hemodialysis patient caused by Delftia acidovorans, previously called Comamonas acidovorans or Pseudomonas acidovorans. The patient had a history of multiple infections of central vascular catheters with other organisms, requiring courses of antibiotics and catheter replacements. Previously reported cases of D. acidovorans infections are reviewed. The isolate appeared to become resistant to cephalosporins after antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
2
35
0
1
Order By: Relevance
“…Although they are ubiquitously distributed in the environment (soil and water), Comamonas and Delftia species are rarely associated with infections in humans. However, several publications have incriminated C. testosteroni and D. acidovorans in particular in human diseases, including severe invasive infections such as bacteremia and meningitis (7,(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Although they are ubiquitously distributed in the environment (soil and water), Comamonas and Delftia species are rarely associated with infections in humans. However, several publications have incriminated C. testosteroni and D. acidovorans in particular in human diseases, including severe invasive infections such as bacteremia and meningitis (7,(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…with antibiotic resistance phenomena has been referenced in the literature but is very limited overall (43)(44)(45). To our knowledge, this is the first report of D. acidovorans tolerance to a broad-spectrum biocide, such as CHX.…”
Section: Discussionmentioning
confidence: 90%
“…Several strains of D. acidovorans (as C. acidovorans) isolated from clinical specimens have been found to be resistant to various groups of antibiotics, such as ␤-lactams, aminoglycosides, and quinolones (43). Chotikanatis et al (44) summarized the previously reported antibiotic susceptibilities of D. acidovorans and concluded that it was resistant to gentamicin in all cases, resistant to all aminoglycosides in some cases, and generally susceptible to cephalosporins, piperacillin, aztreonam, carbapenems, quinolones, and trimethoprim-sulfamethoxazole. A positive correlation between D. acidovorans (as C. acidovorans) and residual chlorine was found in contaminated dental water units, indicating a strong resistance of this bacterium to chlorine (45).…”
Section: Discussionmentioning
confidence: 99%
“…Delftia acidovorans is a low virulence, environmental Gram negative bacillus with a wide geographical distribution, and is an uncommon clinical isolate [1]. Since its initial discovery in 1929 [2], it has been reported with gradual increasing frequency in the academic literature as a pathogenic organism, often in immunocompromised individuals [1].…”
Section: Discussionmentioning
confidence: 99%